Identifying significant contributors for smoking cessation among male prisoners in Australia: results from a randomised clinical trial. Issue 7 (20th July 2020) - Wand, Handan; Richmond, Robyn; Adily, Armita; Le, Andrea; Wilhelm, Kay; Butler, Tony
Abstract : Introduction: In Australia, an estimated 90% of those entering prison are current tobacco smokers and three-quarters of current prisoners are tobacco smokers. Aims: To identify factors and their relative contributions to smoking cessation among male prisoners. Methods: A total of 425 male tobacco smokers with a median age of 32 years in Australian prisons. The primary outcome was continuous abstinence at 3, 6 and 12 months. We measured various sociodemographic characteristics, drug use, psychological distress and the mental and physical health status of the participants. Multivariate logistic regression models and population attributable risks (PAR%) were used to identify the significant factors and their contributions to smoking cessation rates. Results: The median age of participants was 32 years (IQR 25–41 years). High smoking cessation rates were collectively associated with not using drugs, lower psychological distress, good mental health scores and better physical health (PAR%: 93%, 98% and 88% at 3, 6 and 12 months). Conclusion: Our study suggests that not using drugs and being in good mental/physical health are the important contributors to continuous abstinence among prisoners. Thus, effective smoking cessation programmes require a multicomponent approach that includes addressing drug problems and mental health functioning. Trial registration number: 12606000229572.